2011
DOI: 10.1371/journal.pone.0018858
|View full text |Cite
|
Sign up to set email alerts
|

Lhx1 Is Required for Specification of the Renal Progenitor Cell Field

Abstract: In the vertebrate embryo, the kidney is derived from the intermediate mesoderm. The LIM-class homeobox transcription factor lhx1 is expressed early in the intermediate mesoderm and is one of the first genes to be expressed in the nephric mesenchyme. In this study, we investigated the role of Lhx1 in specification of the kidney field by either overexpressing or depleting lhx1 in Xenopus embryos or depleting lhx1 in an explant culture system. By overexpressing a constitutively-active form of Lhx1, we established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 65 publications
3
70
0
Order By: Relevance
“…21 Interestingly, we found that osr1 knockdown completely eliminated lhx1a expression specifically in the presumptive anterior pronephric region of intermediate mesoderm in 15 high-power fields embryos ( Figure 5B; n=15/15), while lhx1a expression in the tail bud of osr1 morphants remained unaltered (data not shown). We therefore tested whether lhx1a might act downstream of osr1 specifically in podocyte development by assaying whether expression of an activated form of Lhx1a (Ldb1-Lhx1; denoted LL-CA) 22 could rescue podocyte differentiation in osr1 morphants. The Lim homeodomain of Lhx1a interacts with the LIM binding protein, Ldb, and this interaction triggers Lhx1a activation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Interestingly, we found that osr1 knockdown completely eliminated lhx1a expression specifically in the presumptive anterior pronephric region of intermediate mesoderm in 15 high-power fields embryos ( Figure 5B; n=15/15), while lhx1a expression in the tail bud of osr1 morphants remained unaltered (data not shown). We therefore tested whether lhx1a might act downstream of osr1 specifically in podocyte development by assaying whether expression of an activated form of Lhx1a (Ldb1-Lhx1; denoted LL-CA) 22 could rescue podocyte differentiation in osr1 morphants. The Lim homeodomain of Lhx1a interacts with the LIM binding protein, Ldb, and this interaction triggers Lhx1a activation.…”
Section: Resultsmentioning
confidence: 99%
“…The Lim homeodomain of Lhx1a interacts with the LIM binding protein, Ldb, and this interaction triggers Lhx1a activation. 22 We expressed a constitutively active Ldb1-Lhx1 protein (LL-CA), which is a fusion of the Ldb1 dimerization domain with the linker, C-terminal and homeodomain of zebrafish Lhx1a. 22 High doses of LL-CA mRNA (320 pg) caused early embryonic lethality associated with failed gastrulation cell movements, consistent with the known role for Lhx1a in gastrulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, A-C). Whole mount in situ hybridization and immunostaining experiments were performed to examine the formation of the pronephros in embryos targeted on one side with 30 ng of Hspa5MO2/embryo using marker genes that include pax2 (44), lhx1 (21,22), and ␤1 subunit of Na/K-ATPase (atp1b1) (45). The marker genes pax2 (60%; 18 of 30), lhx1 (67%; 24 of 36), and atp1b1 (85%; 29 of 34) were strongly suppressed on the injected side but not on the uninjected side (Fig.…”
Section: Hspa5 Function In Pronephros Formationmentioning
confidence: 99%
“…The promoter region of lhx1 contains RAREs, and its expression is directly regulated by the RA signaling pathway (15). In Xenopus embryos, overexpression of lhx1 leads to the expansion of the pronephric field, whereas depletion of lhx1 severely reduces the pronephric field during organogenesis (15,21). In Xenopus, it has been reported previously that RA can induce lhx1 expression in animal caps (23).…”
mentioning
confidence: 99%